On the relationship between long-period comets and large trans-Neptunian planetary bodies. Issue Volume 12:Issue S325(2016) (30th May 2017) - Guliyev, Rustam; Guliyev, Ayyub
Abstract: In the present work we investigate the possible relationship of long-period comets with five large and distant trans-Neptunian bodies (Sedna, Eris, 2007 OR10, 2012 VP113 and 2008 ST291 ) in order to determine the probability of the transfer of a part of these kind of comets to the inner of the Solar System. To identify such relationships, we studied the relative positions of the comet orbits and listed TNOs. Using numerical integration methods, we examined dynamical evolution of the comets and have found one encounter of comet C/1861J1 and Eris.